Well logging and formation evaluation - Darling, Toby (Elsevier ; Gulf Professional Pub., 2005)
The only guide the drilling engineer needs!
Keywords: Geophysical well logging -- Statistical methods.; Geophysical well logging -- Mathematical models.; Prospecting -- Geophysical methods.; elektronické knihy; electronic books